Two (?) Lion Reliefs from Iron Age Moab: Further Evidence for an Architectural and Intellectual Koiné in the Levant? - Weber, Martin (Bulletin of ASOR, 2017)
The collection of the Karak Archaeological Museum contains two carved basalt slabs, both of which show the rear parts and hindquarters of a leonine figure. Although the two slabs differ vastly in their state of preservation, a comparison of their physical properties and iconographic features suggests that the two reliefs originally formed a matching pair and were part of a single architectural feature. Comparing the slabs to the well-known corpus of northern Levantine monumental sculpture, it is argued that the reliefs constitute the remains of two gateway figures, most plausibly dated to the Iron Age. The Karak slabs thus provide the first likely evidence for the use of architectural stone sculpture by Moabite elites, a practice most commonly associated with the Iron Age kingdoms of the northern Levant. Lion sculptures were often employed as gateways figures in public buildings, especially in the northern Levant and northern Mesopotamia, attesting to the close relationship between these images and the royal ideology they helped to project. Through their existence, the Karak slabs not only provide further evidence for cross-cultural artistic interaction in the Iron Age Levant but also suggest that ancient Karak played an important role in these exchanges.